Pengaruh Perceived Uncertainty terhadap Impulse Buying dengan Curiosity sebagai Variabel Mediasi dan Perceived Luck sebagai Variabel Moderasi pada Konsumen Blind Box Generasi Z di Indonesia - Elisabeth Keizha Elvina; Rosa Prafitri Juniarti (Universitas Negeri Surabaya, 2026)
Purchases of blind box products among Generation Z indicate a tendency toward impulsive buying driven by uncertainty regarding product contents. This study aims to examine the effect of perceived uncertainty on impulse buying and to test the roles of curiosity as a mediating variable and perceived luck as a moderating variable. This research adopts a quantitative design. Data were collected through an online questionnaire distributed to Generation Z blind box consumers aged 18–28 years in Indonesia and analysed using PLS-SEM. The results show that perceived uncertainty has a positive and significant effect on both impulse buying and curiosity. However, curiosity does not have a significant effect on impulse buying and therefore does not mediate the relationship between perceived uncertainty and impulse buying. In addition, perceived luck does not significantly moderate the relationship between perceived uncertainty and impulse buying. The findings indicate that product uncertainty can directly trigger impulsive buying behaviour without the involvement of curiosity or perceived luck.